Analisis SWOT dalam Optimalisasi Penyebaran Informasi Internal KG Media - Nurferdiany, Intan Putri; Wijaya, Abung Supama; Marithasari, Harries (Petanda: Jurnal Ilmu Komunikasi dan Humaniora, 2025)
This study aims to analyse the role of KG Media's Public Relations in optimising internal information dissemination through digital communication strategies implemented on the Instagram account @dailyatkgmedia. In addition, this study was conducted to improve on previous research that did not use SWOT analysis to optimise KG Media's internal information dissemination. The method used in this study is descriptive qualitative with data collection techniques in the form of observation, interviews, and active participation of the author during an internship at KG Media. The analysis focuses on how digital communication strategies are used to optimise the dissemination of KG Media's internal information, strengthen internal communication, increase employee engagement, and build organisational identity and culture. The SWOT analysis approach used in this study aims to identify the strengths, weaknesses, opportunities, and threats that affect the effectiveness of KG Media's internal communication strategies. The results of the study show that the main strength of KG Media's Public Relations lies in its ability to utilise digital platforms, produce informative and emotionally valuable content, and keep up with digital trends.